IoT Based Three Phase Fault Analysis for Temporary and Permanent Fault Detection - Buswig, Yonis.M.Yonis; Norain, Binti Sahari; Faridah Hanim, Binti Mohd Noh; Sim, Syi Li; Nur Najiha, Binti Jembari; Wahyu, Mulyo Utomo; Nooradzianie, Muhammad Zin; Nor Aira, Zambri; Farahiyah, Mustafa; Lam, Hong Yin (FAZ Publishing, 2019)
The three phase fault detector and analyse system is designed to differentiate the type of fault occur in power system, enhanced with the Internet of Things (IoT)by using the combinations of Arduino and Wi-Fi module. All sorts of electrical substation that supply the electric to the users like industrial or residential may have some failures due to fault that may be temporary or permanent. However, due to problemslike system take a longer time to detect the type of fault and also required manually to reset off the fault make the existing protection system not efficient in supply energy to consumer. The system can be used three single phase transformers those are wired in star input and star output also three transformers are connected in star input and delta output that having 240 volts input and 12 volts output. Then, ESP NodeMCU is used as controller and also act as device that connect to the IoT system when fault is detected. The devices then link with the Blynk application. User will get the notification from Blynk application when the fault is occurred. Using these devices, user could find automatically after a short-lived interruption in a provisional fault from the tripped situation in case of eternal fault.